(untitled) (Research, Society and Development, 2021)
Due to the COVID-19 pandemic, caused by the new coronavirus, adaptations have been made around the world so that it would be possible to live with this virus while scientists are looking for an effective way to combat it. In dentistry, dental surgeons had to reinvent themselves in their procedures in order to be carried out safely, adding new biosafety measures. The objective of the present survey was to carry out an integrative review of the current literature in order to understand the effect of the coronavirus regarding the introduction of new biosafety measures for dental care, considering the benefits, limitations and impacts for society. It is an integrative literature review that was based on a bibliographic search of articles, in the databases PubMed, LILACS, BVS, Scopus and Cochrane Library. After the eligibility criteria, 15 articles were included, 11 published in English, 2 in Portuguese and 2 in Spanish. After analyzing the articles, their respective syntheses were presented on a board. Herewith, it is concluded that the benefits of using biosafety equipment and strategies, especially personal protective equipment (PPE) and social isolation are paramount to well-being. In addition, the theme addressed in this work becomes indispensable, since biosafety actions have always been sought in order to reduce infectious contagious contamination and especially at the present time.